On the Necessity of Systematically Planning Clinical Tumor Documentation - Knaup, P.; Harkener, S.; Ellsässer, K.-H.; Haux, R.; Wiedemann, T. (Methods of Information in Medicine, 2001)
Tumor documentation is an important task for both clinical research and patient care. Documentation systems for these purposes have to be planned systematically and should be goal oriented. We applied the method of a so-called ‘standardized documentation protocol’ for systematically planning two documentation systems in oncology: one for the tumor center Heidelberg/Mannheim and the other for a nationwide project in the field of documentation and therapy planning in pediatric oncology. The method proved to be helpful in both cases even though the resulting documentation protocols are completely different and although they served different objectives. Therefore, the aim of the paper is to motivate and help medical informatics professionals to systematically plan other documentation systems using this method.
Keywords: Tumor Documentation; Electronic Patient Record; Tumor Center; Systematic Planning; Clinical Research